Предмет: Алгебра,
автор: kolvr123
(5-х)(3х+1)=(2х-1)(15-4х) помогите пожалуйста. Заранее спасибо
Ответы
Автор ответа:
1
( 5 - х )( 3х + 1 ) = ( 2x - 1 )( 15 - 4x )
15x + 5 - 3x^2 - x = 30x - 8x^2 - 15 + 4x
- 3x^2 + 14x + 5 = - 8x^2 + 34x - 15
8x^2 - 3x^2 - 34x + 14x + 15 + 5 = 0
5x^2 - 20x + 20 = 0
5( x^2 - 4x + 4 ) = 0
( x - 2 )^2 = 0
x - 2 = 0
x = 2
15x + 5 - 3x^2 - x = 30x - 8x^2 - 15 + 4x
- 3x^2 + 14x + 5 = - 8x^2 + 34x - 15
8x^2 - 3x^2 - 34x + 14x + 15 + 5 = 0
5x^2 - 20x + 20 = 0
5( x^2 - 4x + 4 ) = 0
( x - 2 )^2 = 0
x - 2 = 0
x = 2
Похожие вопросы
Предмет: Литература,
автор: chervak5
Предмет: Геометрия,
автор: Аноним
Предмет: Математика,
автор: svetasosipisos
Предмет: Обществознание,
автор: 79210696544
Предмет: Литература,
автор: dayana2017